The Limitations and Potentials of Evaluating Economic Aspects of Community-Based Health Promotion: A Critical Review - Philipp Weber; Leonie Birkholz; Riccarda Straub; Simone Kohler; Natalie Helsper; Lea Dippon; Klaus Pfeifer; Alfred Rütten; Jana Semrau (Applied Health Economics and Health Policy, 2024)
Community-based health promotion (CBHP) interventions are promising approaches to address public health problems; however, their economic evaluation presents unique challenges. This review aims to explore the opportunities and limitations of evaluating economic aspects of CBHP, focusing on the assessment of intervention costs and outcomes, and the consideration of political-level changes and health equity. A systematic search of the PubMed, Web of Science and PsycInfo databases identified 24 CBHP interventions, the majority of which targeted disadvantaged communities. Only five interventions included a detailed cost/resource assessment. Outcomes at the operational level were mainly quantitative, related to sociodemographics and environment or health status, while outcomes at the political level were often qualitative, related to public policy, capacity building or networks/collaboration. The study highlights the limitations of traditional health economic evaluation methods in capturing the complexity of CBHP interventions. It proposes the use of cost-consequence analysis (CCA) as a more comprehensive approach, offering a flexible and multifaceted assessment of costs and outcomes. However, challenges remain in the measurement and valuation of outcomes, equity considerations, intersectoral costs and attribution of effects. While CCA is a promising starting point, further research and methodological advancements are needed to refine its application and improve decision making in CBHP.
Keywords: 610